Fault protection of multiterminal HVDC networks: Impact of inductance. (October 2022) - Yang, Chao; Xin, Ying; Li, Chao; Li, Quan; Yang, Tianhui; Lu, Jianing; Xiong, Jialing; Wang, Changqi; Li, Bin
Highlights: Inductance is an indispensable element for SFCLs in a multiterminal HVDC system. Inductance can curb the rising rate of fault current at the early stage of a fault. Resistance can effectively reduce the amplitude of lasting fault current. Converter in a multiterminal HVDC system cannot be locked until a fault is cleared. SFCL with proper resistor and inductor is suitable for multiterminal HVDC systems. Abstract: Multiterminal Voltage Source Converter (VSC) High Voltage Direct Current (HVDC) networks are developing rapidly worldwide, especially in China with urgent needs of long-distance power transmission. Currently, the interrupting capacity of available DC circuit breakers (DCCBs) is a key obstacle to the development of multiterminal VSC HVDC networks. Superconducting fault current limiters (SFCLs) can compensate for the limitation of DCCBs. Conventionally, a resistive SFCL is regarded as essential and sufficient, while an inductive one is less related and optional. However, pure resistance cannot effectively suppress the rising rate of fault current at the very early stage of a fault, resulting in unnecessary blocking of the converter. Adequate inductance is required for such SFCLs to curb rapidly increasing fault currents within the first few milliseconds, which is critical to DCCBs to isolate fault without interrupting other DC transmission lines. In this paper, we compared and analyzed the performances of SFCLs with different resistances and inductances in a four-terminal VSC HVDC network using PSCAD/EMTDC software. The results indicate that even resistance and inductance show different current limiting effects, but they are both necessary to realize effective SFCL function for multiterminal VSC HVDC networks. The outcomes of this paper are of significance in FCL design for multiterminal VSC HVDC networks.